Serine-associated one-carbon metabolic reprogramming: a new anti-cancer therapeutic strategy - Zhang, Jing; Bai, Jian; Gong, Chen; Wang, Jianhua; Cheng, Yi; Zhao, Jing; Xiong, Huihua (Frontiers in Oncology, 2023)
Tumour metabolism is a major focus of cancer research, and metabolic reprogramming is an important feature of malignant tumours. Serine is an important non-essential amino acid, which is a main resource of one-carbon units in tumours. Cancer cells proliferate more than normal cells and require more serine for proliferation. The cancer-related genes that are involved in serine metabolism also show changes corresponding to metabolic alterations. Here, we reviewed the serine-associated one-carbon metabolism and its potential as a target for anti-tumour therapeutic strategies.